A Pilot Study on E-Learning Applications and its Effectiveness in B-Schools & Universities - Rao, Vasudha; Kulkarni, Vaishali (SFIMAR Research Review, 2011)
E-learning is becoming a dominant delivery method in B-schools, Universities across the country. Although many institutions are recognizing the potential of e-learning to bring learning closer to students, there appears to be some issues to be addressed in delivering e-learning. Learners still face some barriers to e-learning, such as situational, organizational, and technical barriers. Institutes are also concerned about cost and technology requirements for implementing e-learning. Moreover, there is a plethora of emerging technologies that have implications for campus learning. To effectively navigate through this era of e-learning, an understanding of the current state and the future directions of e-learning is warranted. This study aims to measure effectiveness of e-learning programs and applications in various institutes and organizations.